Internet Portal for Evaluation of Solar and Wind Energy Resources (Global Journals of Research in Engineering, 2023)
This scientific paper presents the results of using the software called Internet Portal for Renewable Energy developed at the State Energy Institute of Turkmenistan for a quick and accurate assessment of solar and wind energy resources in Turkmenistan Studies have shown that the use of a software product allows you to quickly determine the resources of solar and wind energy in a given coordinate which in turn affects the efficiency of the construction of the station
Keywords: internet portal; renewable energy; source of solar and wind energy; Turkmenistan